Antimicrobial effects of essential oil from Origanum vulgare in combination with conventional antibiotics against Staphylococcus aureus - De Rose, Elisabetta; D’Aquila, Patrizia; Sena, Giada; Perrotta, Annamaria; Passarino, Giuseppe; Bellizzi, Dina (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAntimicrobial resistance is emerging as a significant threat to public health, prompting the search for novel natural molecules, such as Essential Oils (EOs), that can affect, alone or in combination with conventional antibiotics, growth and various biological activities in microorganisms.MethodsFirst, the effects of ten essential oils extracted from aromatic plants grown in Calabria (Southern Italy) and seven conventional antibiotics against Staphylococcus aureus cells were studied individually, determining the Minimum Inhibitory Concentrations (MICs) through broth microdilutions. Subsequently, limited to Origanum vulgare EO (OEO) only, the compounds were evaluated in combination through checkerboard and time kill assays. ZIP synergy scores and Fractional Inhibitory Concentrations Indexes (FICI) were calculated to determine the interactive effects of the combinations. At 0.5 x MIC concentration values of OEO-antibiotic combinations, the biofilm and the expression of genes involved in the Quorum Sensing (QS) process were determined by the crystal violet method and quantitative real-time PCR reactions, respectively. At the same concentrations, adenine and cytosine methylation levels were quantified through ELISA.ResultsThe results showed that S. aureus was highly sensitive only to OEO, in which a small MIC value was noticed (0.312 mg/mL). Synergistic effects were observed when combining OEO and ampicillin, gentamicin, tetracycline, and tobramycin, resulting in reductions of antibiotic MICs. An inhibition of biofilm formation and a general down-regulation of the expression of agrA, hld, RNAIII, and rot genes were observed. Similarly, up- and down-methylation of cytosines and adenines, respectively, compared to antibiotics alone was noticed.ConclusionsTaken together, our observations provide evidence on the role of the OEO-antibiotic combinations in enhancing the action of antibiotics on the growth and suggest that these combinations could influence biological processes such as biofilm formation, QS, and epigenetic changes.